Clinical manifestation and management of ADPKD in Western countries - Sommerer, Claudia; Zeier, Martin (Kidney diseases, 2016)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease in Western countries. The prevalence is between 2.4/10,000 and 3.9/10,000. ADPKD represents a systemic disease resulting in deterioration in renal function. Until now, mutations in two genes (PKD1 and PKD2) have been identified. Recently, the European Medicines Agency (EMA) approved the use of the vasopressin V2 receptor antagonist tolvaptan to slow the progression of cyst development and renal insufficiency connected with ADPKD in adult patients with chronic kidney disease stages 1-3 at initiation of treatment with evidence of rapidly progressing disease. Whereas the EMA approved the release of tolvaptan, the US Food and Drug Administration (FDA) requested further data on side effects and the selection of patient cohorts who may benefit from treatment. Summary: This review focused on advances in the management and treatment of ADPKD in Western countries. Key Message: ADPKD represents the fourth most common cause of end-stage renal disease (ESRD) in Western countries. ADPKD is a multisystemic disease characterized by the progressive development of bilateral renal cysts, resulting in enlargement of the kidney volume due to cystic formations, hypertension, hematuria, and loss of renal function. ADPKD is associated with high inter- and intrafamilial variability in disease appearance and progression. Patients with PKD1 mutations typically have a more severe phenotype than those with PKD2 mutations. ADPKD is under intensive investigation. Vasopressin and the associated cyclic adenosine monophosphate-related signaling pathways have been demonstrated to be important contributors to cyst growth in ADPKD. Supportive treatments are recommended with the aim of reducing morbidity and mortality associated with disease manifestations. In the past years, several agents have been investigated in ADPKD patients, including mTOR inhibitors, somatostatin analogs, statins, and vasopressin V2 receptor antagonists. Facts from East and West: (1) ADPKD is diagnosed globally by ultrasound detection of kidney enlargement and presence of cysts. Recent analyses of variants of the PKD1 and PKD2 genes by next-generation sequencing in Chinese and Western ADPKD patients might lead to the development of reliable genetic tests. (2) Besides lifestyle changes (low-salt diet, sufficient fluid intake, and no smoking), blood pressure control is the primary nonspecific treatment recommended by Kidney Disease - Improving Global Outcomes (KDIGO) for ADPKD patients. How low the blood pressure target should be and what the means of achieving it are remain open questions depending on the severity of chronic kidney disease and the age of the patients. In a recent Chinese study, diagnostic needle aspiration and laparoscopic unroofing surgery successfully improved infection, pain, and hypertension. Peritoneal dialysis was found to be a feasible treatment for most Chinese ADPKD patients with ESRD. In most Western centers, patients without contraindication are selected for peritoneal dialysis. Kidney transplantation with concurrent bilateral nephrectomy was successful in relieving hypertension and infection in Chinese ADPKD patients. In Western countries, sequential surgical intervention with kidney transplantation after nephrectomy, or the other way round, is preferred in order to reduce risks. (3) The vasopressin 2 receptor antagonist tolvaptan was approved in Europe, Canada, Japan, and Korea to slow down progression of kidney disease in ADPKD patients. Tolvaptan is not yet approved in the USA or in China. mTOR pathway-targeting drugs are currently under evaluation: mTOR inhibitors could slow down the increase in total kidney volume in a cohort of Western and Japanese ADPKD patients. Western studies as well as an ongoing study in China failed to show benefit from rapamycin. A study performed in Italy indicates protective effects of the somatostatin analog octreotide in ADPKD patients. Western and Chinese studies revealed a potential beneficial effect of triptolide, the active substance of the traditional Chinese medicine Tripterygium wilfordii (Lei Gong Teng) to prevent worsening in ADPKD patients.
Gesehen am 12.05.2020